Enhancing rapid diagnosis of pulmonary embolism in the emergency department: the critical role of point-of-care ultrasound (POCUS)—a systematic review and meta-analysis - Hany A. Zaki; Benny Ponappan; Eman E. Shaban; Ahmed Shaban; Amira Shaban; Ahmed Khan; Kaleem Basharat; Mohammed F. Abosamak (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Point-of-care ultrasound (POCUS), performed at the patient’s bedside, has been widely used to diagnose several medical conditions. However, its accuracy in diagnosing pulmonary embolism (PE) in the emergency department (ED) is not fully established. Therefore, the current meta-analysis examined the accuracy of POCUS in diagnosing PE in the ED. Results A total of fourteen studies involving 1835 patients suspected of PE were included. The pooled results showed that lung ultrasound has a sensitivity and specificity of 47% and 88%, respectively. The most frequently used clinical sign for diagnosing PE using lung ultrasound was the presence of at least one hypoechoic pleural-based lesion. The pooled results also showed that deep venous ultrasound, which mostly used the bilateral compression of the femoral and popliteal veins, yielded a sensitivity of 56% and a specificity of 96% for PE. In addition, cardiac ultrasound yielded a sensitivity of 39% and specificity of 94% for PE, with the most frequently used clinical sign being right ventricular (RV) dilation. On the other hand, multiorgan POCUS displayed a sensitivity of 79% and specificity of 79%. Conclusion Cardiac, lung, and deep venous ultrasounds have consistently shown high specificity, making them valuable diagnostic tools for ruling in PE at the patient’s bedside. On the other hand, multiorgan POCUS displayed high diagnostic accuracy, making it a valuable tool for confirming or dismissing PE in ED.